2019
DOI: 10.1016/j.microc.2019.03.035
|View full text |Cite
|
Sign up to set email alerts
|

The potential of triterpenoids as chemotaxonomic tools to identify and differentiate genuine, adulterated and archaeological balsams

Abstract: Plant exudates have been extensively used in the past for different applications related to their olfactory, physical or medical properties. Their identification in archaeological samples relies, notably, on the characterisation of chemotaxonomic molecular markers but is often hampered by the severe alteration of their typical genuine molecular signature due to ageing. Among these exudates, those recovered from Styrax, Liquidambar and Myroxylon tree species-defined as balsams-have been exploited in the past fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Some of the difference may also be due to variation of the plant material source. However, given the volatility and instability of the main constituents and the large age difference between the samples, at least some of the differences in composition are likely due to degradation processes (Courel et al 2019).…”
Section: Variation Of the Proportions Of Benzyl Estersmentioning
confidence: 99%
“…Some of the difference may also be due to variation of the plant material source. However, given the volatility and instability of the main constituents and the large age difference between the samples, at least some of the differences in composition are likely due to degradation processes (Courel et al 2019).…”
Section: Variation Of the Proportions Of Benzyl Estersmentioning
confidence: 99%
“…Although results of patch testing with gum mastic have rarely been published, patch testing with gum storax has been more widely performed. 23,24 The composition of gum storax (L. styraciflua), including its triterpenes 38 and volatile fraction, is considerably different from gum mastic. Ingredients identified in the volatile fraction of at least 2 of 3 reviewed studies [38][39][40] include cinnamyl cinnamate, 3-phenylpropyl cinnamate, cinnamic acid, cinnamyl alcohol, 3-phenylpropyl alcohol, β-caryophyllene, caryophyllene oxide, styrene, benzyl cinnamate, β-pinene, acetophenone, p-ethylphenol, and α-cubenene.…”
Section: Patientmentioning
confidence: 99%
“…The flowers of S. tonkinensis are in strings with a light fragrance and can be used as medicine to relieve pain [ 14 ]. Its bark is the source of benzoin, which can be used as a flavoring agent and can produce incense, perfume, and medicine [ 15 , 16 ]. Previous research has indicated that the FA concentration in S. tonkinensis seeds is high, and the UFA concentration increases with seed development, while the saturated fatty acid (SFA) concentration decreases [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%